Interest rate risk management : a case study of GBS Mutual Bank - Williamson, Gareth Alan (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2008)
Banks play a pivotal role in the economic growth and development of countries, primarily through the diversification of risk for both themselves and other economic agents. Interest rate risk is regarded as one of the most prominent financial risks faced by a bank. A large portion of private banks' revenue stems from net interest income that is generated from the difference between various assets and liabilities that are held on the balance sheet. Fluctuations in the interest rate can alter a bank's interest income and value, making interest rate risk management vital to its success. The asset and liability committee of a bank is the internal committee charged with the duty of managing the bank's interest rate risk exposure through the use of various hedging strategies and instruments. This thesis uses a case study methodology to analyse GBS Mutual Bank interest rate risk management. Its specific business circumstances, balance sheet structure and the market conditions over a specified period are used to comment on the practicality of a variety of balance sheet positioning strategies and derivative hedging instruments. The thesis also provides recommendations for the bank's asset and liability committee in terms of its functions and organisation. It is elucidated that the most practical balance sheet hedging strategies are a volume strategy and immunisation, while the most practical derivative hedging instruments are interest rate futures and interest rate collars. It is found that the bank has a well functioning asset and liability committee whose only encumbrance to its functionality is the inadequacy of the informational technology used to measure, control and manage its interest rate risk position. This thesis concludes by summarising the practicality of the various interest rate risk hedging alternatives available to the GBS Mutual Bank. Implementing a particular strategy or instrument depends, of course, on its asset and liability committee's decision.
Keywords: GBS Mutual Bank; Interest rates -- Case studies; Interest rate risk -- Case studies; Risk management -- Case studies; Financial risk -- Case studies; Banks and banking -- Case studies